Non-alcoholic fatty liver disease severity is modulated by transglutaminase type 2 - Piacentini, Mauro (Cell Death Dis, 2018)
Non-alcoholic fatty liver disease (NAFLD) is one of the most important liver diseases worldwide. Currently, no effective treatment is available, and NAFLD pathogenesis is incompletely understood. Transglutaminase type 2 (TG2) is a ubiquitous enzyme whose dysregulation is implicated in the pathogenesis of various human diseases. Here we examined the impact of TG2 on NAFLD progression using the high-fat-diet-induced model in both wild-type and TG2-deficient mice. Animals were fed with a standard chow diet or a high-fat diet (42% of the energy from fat) for 16 weeks. Results demonstrated that the absence of a functional enzyme, which causes the impairment of autophagy/mitophagy, leads to worsening of disease progression. Data were confirmed by pharmacological inhibition of TG2 in WT animals. In addition, the analysis of human liver samples from NAFLD patients validated the enzyme’s involvement in the liver fat disease pathogenesis. Our findings strongly suggest that TG2 activation may offer protection in the context of NAFLD, thus representing a novel therapeutic target for tackling the NAFLD progression.